Investigation of the complete blood count parameters as an early diagnostic tool in contrast-induced nephropathy after contrast-enhanced computed tomography - Tezel, Onur; Bilge, Sedat (Annals of Medical Research, 2021)
Aim: We investigated complete blood count parameters as inflammatory biomarkers and compared these to serum creatinine values as early diagnostic criteria of ongoing contrast-induced nephropathy. Contrast-induced nephropathy is an important cause of acute kidney injury. Early diagnosis can reduce morbidity and mortality. There is no clear predictor parameter for the early diagnosis of contrast-induced nephropathy.Material and Methods: Patients who underwent contrast-enhanced computed tomography examination were included in this retrospective study. Contrast-induced nephropathy was defined as 25%, a higher increment or a 0.5 mg/dL elevation above the baseline serum creatinine levels within 72 hours. Patients were divided into contrast-induced nephropathy and non-contrast-induced nephropathy groups. The complete blood count parameters obtained before and within the first 24 hours after contrast-enhanced computed tomography were compared between groups. Results: The post-contrast-enhanced computed tomography neutrophil-to-lymphocyte ratio values were significantly higher in the contrast-induced nephropathy group compared to the non-contrast-induced nephropathy group (11.85±1.56 vs 7.29±0.49; p = 0.000). Comparison of the post-contrast-enhanced computed tomography values of the platelet-to-lymphocyte ratio, mean platelet volume-to-platelet count ratio, and lymphocyte to monocyte ratio revealed no statistically significant differences between the groups (p = 0.283, 0.128, and 0.792 respectively).Conclusions: An increased neutrophil-to-lymphocyte ratio level after a contrast-enhanced computed tomography procedure is associated with the development of contrast-induced nephropathy. The use of the neutrophil-to-lymphocyte ratio in the emergency department as a predictive parameter can significantly improve the diagnostic process, favorably acting on the prognosis of patients developing contrast-induced nephropathy.
Keywords: Acute kidney injury; contrast agents; emergency department; inflammatory biomarkers; neutrophil-to-lymphocyte ratio